Moral leadership in an age of accountability: reconciling contrasting imperatives: A study of executive headteachers in England - Belcher, Daniel (2021)
This thesis explored how moral leadership was understood and enacted by executive headteachers working in an age of high accountability in England. The research investigated leaders’ moral frameworks, the moral tensions experienced in their roles and how they sought to reconcile any tensions between the moral and accountability imperative. The focus responded to growing calls for a reassertion of moral leadership in education and amid concerns that the accountability system is having a detrimental effect, constraining leaders and rewarding unethical practices.